Chronic Stress: Impacts on Tumor Microenvironment and Implications for Anti-Cancer Treatments - Tian, Wentao; Liu, Yi; Cao, Chenghui; Zeng, Yue; Pan, Yue; Liu, Xiaohan; Peng, Yurong; Wu, Fang (Frontiers in Cell and Developmental Biology, 2021)
Chronic stress is common among cancer patients due to the phycological, operative, or pharmaceutical stressors at the time of diagnosis or during the treatment of cancers. The continuous activations of the hypothalamic-pituitary-adrenal (HPA) axis and the sympathetic nervous system (SNS), as results of chronic stress, have been demonstrated to take part in several cancer-promoting processes, such as tumorigenesis, progression, metastasis, and multi-drug resistance, by altering the tumor microenvironment (TME). Stressed TME is generally characterized by the increased proportion of cancer-promoting cells and cytokines, the reduction and malfunction of immune-supportive cells and cytokines, augmented angiogenesis, enhanced epithelial-mesenchymal transition, and damaged extracellular matrix. For the negative effects that these alterations can cause in terms of the efficacies of anti-cancer treatments and prognosis of patients, supplementary pharmacological or psychotherapeutic strategies targeting HPA, SNS, or psychological stress may be effective in improving the prognosis of cancer patients. Here, we review the characteristics and mechanisms of TME alterations under chronic stress, their influences on anti-cancer therapies, and accessory interventions and therapies for stressed cancer patients.